Bread and Steelbands - Unknown (Trinidad Guardian)
A National Consultation on Steelband on January 29th to 31st will provide opportunity for persons involved in the propagation of the national art form to air their views and put forward constructive proposals on the way it should go. It is aimed at arriving at consensus on an action programme while providing its practitioners with employment opportunities. Also, the urgent need for steps to protect the steelbandsmen from exploitation and the exploitation of the steelband for the benefit of the country.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago -- History